The Role of Social Media Marketing in Enhancing Customer Loyalty in the Manufacturing Industry - Lasnoto; Burhanuddin; Sijanto, Adi (Yayasan Pendidikan Belajar Berdikari, 2024)
Social media marketing (SMM) has emerged as a crucial strategy for manufacturing businesses to enhance customer loyalty in the era of digitalization and heightened competition. This study explores the role of SMM in fostering strong customer relationships and its impact on customer loyalty in the manufacturing sector. A comprehensive literature review reveals that effective SMM activities, characterized by support, openness, empathy, and positive attitudes, significantly contribute to building brand trust and customer loyalty. User-generated content and emotional connections developed through brand social network websites also play a vital role in enhancing consumer-community identification and repurchase intentions. Furthermore, the study highlights the importance of effective communication, including friendly demeanor and nonverbal cues, in increasing customer satisfaction and loyalty. However, research gaps remain in understanding the direct impact of key elements of SMM on customer loyalty in the manufacturing industry. The study emphasizes the need for quantitative analysis and measurement techniques to provide deeper insights into this relationship. Additionally, the integration of emotional intelligence and artificial intelligence in public relations has shown promising results in enhancing customer loyalty in the manufacturing sector. The findings underscore the significance of investing in effective SMM strategies to build strong customer relationships, drive satisfaction, and foster loyalty in the manufacturing industry.